Transcriar para traduzir: o caso do elemento voz em Macbeth, e suas possibilidades tradutórias para o cinema de Orson Welles - Araujo, Romero Caio Leandro (2024)
The following dissertation aims to unravel the possibilities of translating the poetic element of voice, which belongs to Shakespearean theater, into filmic language. For this debate, Orson Welles' 1948 film Macbeth is used as the object of research. The dissertation will work along three key paths: the first will be an analysis of Elizabethan theater, its characterizations and historical echoes; as well as a reflection on Orson Welles' vision as an author-translator, who would establish himself, over time, as a transmedia artist, navigating simultaneously between theater, radio and cinema and frequently translating literary works into these media. Secondly, we will explore the idea of film montage attached to scenography and its use as a translating engine for this poetic voice element, with Einsenstein's intellectual montage (COSTA, 2003) being a fundamental component in Welles' translation. In the third and final section, we discuss the effects of transcreation provided by montage as a translation resource. In other words, we try to understand this translation in its praxis. Here, the concept of transcreation created by Haroldo de Campos based on his translation experiences, and the concept of semiosphere created by Lotman, as well as Max Bense's concepts of natural and artificial poetry, will be fundamental to understanding the translation of this poetic sign into cinema.